The effectiveness of a local wisdom-based learning model in drama script writing: a mixed-methods study - Eggie Nugraha Eggie; Lili Sadeli (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Drama script writing in higher education often emphasizes technical structure while underutilizing students’ cultural knowledge as a creative resource. Integrating local wisdom into writing instruction may strengthen both dramaturgical competence and cultural literacy. This study investigates the effectiveness of a local wisdom based learning model in improving drama script writing among language education students. A mixed methods approach using a sequential explanatory design was employed with 35 undergraduate students. Quantitative data were collected through document analysis, engagement observation, questionnaires, and pre and post script assessment. Qualitative data from interviews and script analysis were used to explain quantitative patterns. Instructional planning demonstrated substantial integration of local wisdom, and students showed high engagement during culturally grounded activities. Script scores improved significantly from a mean of 68 to 82, indicating measurable gains in conflict development, characterization, and structural coherence. Qualitative findings revealed that cultural values functioned as structural drivers of dramatic conflict rather than decorative themes. The findings suggest that structured integration of local wisdom can enhance drama writing competence while deepening students’ cultural literacy within a specific higher education context. The study contributes to culturally sustaining pedagogy by clarifying how local cultural knowledge may operate as a pedagogical resource in creative writing instruction.